(untitled) (Journal of Computational Mathematics, 2021)
In this paper, the numerical solution of the matrix problems over a ring of integers is discussed. The rank-k updating algorithm for the exact inversion of a matrix is proposed. This algorithm is generally more effective than Jordan elimination. The common divisor of the numbers involved is reduced to avoid over-swelling of intermediate numbers.